Performance Analysis Of Blockchain Networks In A Healthcare Context - Almeida, Suzana P.; Praxedes, Washington Luiz de L.; Hollanda, Leone B.; Souza, Cidcley T. de; Rodrigues, Antonio Wendell de O. (Anais da Escola Regional de Alto Desempenho da Região Nordeste (ERAD-NE), 2025)
The purpose of this work is to analyze the performance of two different blockchain networks in the context of healthcare applications. Blockchain networks are known for their decentralized structure, resiliency, and tamperproofness. Hyperledger Fabric and Ethereum were used to benchmark and compare its performance in two scenarios for a simple blockchain smart contract that stores patient image data. The results showed a slight advantage for Ethereum in increased load tests and it also obtained a lower degree of variation during these tests.